Cowden syndrome—a case report emphasizing the role of the dental surgeon in diagnosis. (15th July 2014) - Webber, Liana Preto; Martins, Manoela Domingues; Carrard, Vinícius Coelho; Trevizani Martins, Marco Antônio; Munerato, Maria Cristina
ABSTRACT Cowden syndrome or multiple hamartoma syndrome, is a rare genetic condition inherited in an autosomal dominant pattern characterized by cutaneous manifestations, polyps, thyroid gland neoplasias, and macrocephaly. This report presents the case of a 36‐year‐old patient who looked for dental treatment for a gingival nodule. Current and past medical history and oral and facial manifestations led to the diagnosis of Cowden syndrome. This case report emphasizes the role of the dental surgeon in the diagnosis of this systemic disease, based on the analysis of medical history and manifestations in the oral cavity.